Perbandingan Keanekaragaman Spesies Burung antara Wilayah Rural dan Urban: Studi Kasus di Desa Taji, Juwiring, dan Kelurahan Gergunung, Klaten Utara: Penelitian - Dwi Purwa Saputra, Arendra; Afrida Saleh, Dinara; Restu Pinasti, Latifah; Aqila Shandy Prabowo, Ghazy (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study compares bird diversity in rural areas (Taji and Juwiring Villages) and an urban area (Gergunung Subdistrict) in Klaten Regency. Observations were carried out using the point count method at 82 stations during morning and afternoon peak activity. Data were analyzed using the Shannon-Wiener diversity index and relative density. The results indicate that the urban area had moderate diversity (H’ = 1.89) supported by heterogeneous microhabitats and the presence of green open spaces. Conversely, the rural area showed low diversity (H’ = 0.96) with strong dominance of the Java Sparrow (>70% of individuals), reflecting homogeneous agricultural landscapes and low vegetation complexity. These findings highlight that habitat structure and quality play a more substantial role than rural–urban classification in shaping bird community composition. Enhancing vegetation complexity and habitat availability is essential to support sustainable bird populations across.